Pertanggungjawaban Pidana Terhadap Wanita dalam Perdagangan Narkotika (Studi Putusan No reg. 533 / Pid.Sus / 2013 / PN.TK) - Zainab Ompu Jainah (KEADILAN PROGRESIF, 2016)
Narcotics is a violation of the law and violation of social norms that have been around a long time in line with the development of other crimes such as prostitution, gambling, and others. The research problem is how the criminal accountability for perpetrators of drug trafficking carried out by a woman? Juridical normative and empirical approach, the data used is qualitative analysis. Based on the research panel of judges in the trial of the case of narcotics, with No. reg. 533 / Pid.Sus / 2013 / PN.TK verdict for NUR is we Als MILA proven legally and convincingly guilty of committing a crime "without authority or unlawfully distribute Narcotics Group 1 in the form of plants weighing not exceed five (5) grams of" as regulated and punishable under Article 114 Paragraph (2) of Law Number 35 year 2009 on Narcotics, convict the defendant imprisonment for 15 (fifteen) years fine of Rp 4000,000,000, - (four billion rupiah) subsidiary 6 (six) months imprisonment. With the consideration that in view of the crime of drugs and psychotropic substances included in a special type of criminal offense then criminal sanctions can be imposed against cumulatively by dropping two principal types of criminal as well, such as imprisonment and criminal fines or capital punishment and criminal penalties. Suggestions, for law enforcement should be the rule of law as stipulated in the Law on Narcotics, it is expected that law enforcement officers can reveal all the perpetrators of drug crimes so that it can be judged without any remaining.